374 تقييم أثر انضمام مصر لتجمع بريكس على أداء الاقتصاد الكلي والقطاع الزراعي المصري : Assessing The Impact of Egypt's Accession to The BRICS Group on The Performance of The Egyptian Macroeconomy and Agricultural Sector - هدي النمر نيفين كمال، بركات الفرا وأخرون (معهد التخطيط القومي, 2026)
هدفت الدراسة إلى تقييم تأثير انضمام مصر إلى تجمع بريكس على الاقتصاد الكلي وقطاع الزراعة. أظهرت النتائج الأهمية الاقتصادية الكبيرة لتجمع بريكس عالميًا. كما كشفت عن وجود عجز في الميزان التجاري الزراعي المصري مع دول التجمع. وأوضحت النماذج أن خفض الحواجز التجارية قد يحسن مؤشرات الاقتصاد والإنتاج الزراعي في مصر. وقدمت الدراسة مقترحات لتعزيز الصادرات الزراعية والغذائية إلى أسواق بريكس. The study examined the impact of Egypt’s accession to BRICS on the economy and agriculture. Results highlighted the significant global economic role of BRICS. The analysis revealed an agricultural trade deficit between Egypt and BRICS countries. Reducing trade barriers is expected to improve economic and agricultural performance in Egypt. The study proposed policies to strengthen agricultural and food exports to BRICS markets.